PENGARUH VARIABEL KEUANGAN DAN NON KEUANGAN TERHADAP UNDERPRICING SAHAM SAAT IPO DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Dewi, Susana; Siti Septiyanti; Edi Sutanto; Hanifah; Firmansyah; Herlina (Universitas La Tansa Mashiro, 2025)
This study aims to analyze the impact of financial and non-financial variables on stock underpricing during the Initial Public Offering (IPO) on the Indonesia Stock Exchange in the period 2020 to 2024. The financial variables studied include Return on Assets (ROA), Return on Equity (ROE), and Company Size, while non-financial variables include Underwriter Reputation and Company Age. The method applied was a quantitative approach with panel data regression analysis and processed with the Eviews 12 Software tool. The population of this study is 278 IPO companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The sample in this study consisted of companies that conducted IPOs during the period, as many as 38 companies were selected through purposive sampling techniques with 190 company data. The results show that partially Return on Assets (ROA), Return on Equity (ROE), and Company Size and Underwriter Reputation have a significant influence on stock underpricing. On the other hand, the Age of the Company did not show any significant influence that was meaningful individually. This study presents the impact for investors, companies issuing shares, and underwriters in recognizing the elements that affect the determination of stock prices during initial public offerings.